2018
DOI: 10.3390/cryst8120469
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Crystal Surface on the Austenitic and Martensitic Phase Transition in Pure Iron

Abstract: Using classical molecular dynamics simulations, we studied the influence that free surfaces exert on the austenitic and martensitic phase transition in iron. For several single-indexed surfaces—such as ( 100 ) bcc and ( 110 ) bcc as well as ( 100 ) fcc and ( 110 ) fcc surfaces—appropriate pathways exist that allow for the transformation of the surface structure. These are the Bain, Mao, Pitsch, and Kurdjumov–Sachs pathways, respectively. Tilted surfaces follow the pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(48 citation statements)
references
References 43 publications
10
38
0
Order By: Relevance
“…The occurrence of the transformation depends in particular on the surface orientation chosen and the thin-film thickness. In previous work [39], we showed that the martensitic transition temperature of ideal thin films decreases with the thin-film thickness, such that the transformation does not occur at all for films that are too thick; this is the case in the present study.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…The occurrence of the transformation depends in particular on the surface orientation chosen and the thin-film thickness. In previous work [39], we showed that the martensitic transition temperature of ideal thin films decreases with the thin-film thickness, such that the transformation does not occur at all for films that are too thick; this is the case in the present study.…”
Section: Resultssupporting
confidence: 60%
“…We find these Kurdjumov-Sachs orientation relationships obeyed in most material nucleated in the vicinity of the dislocations; occasionally, the Nishiyama-Wassermann orientation relationships [46,47] While the local nuclei lead to the observation of Kurdjumov-Sachs and Nishiyama-Wassermann orientation relationships, the final structure of the new phase is governed by a different principle based on the proposition that the free surface of the thin film must be conserved over the transformation [39]. We call, for simplicity, the final evolving structure the 'global phase', as it will eventually cover all of the thin film and was encountered in all cases studied here irrespective of the initial dislocation density.…”
Section: The Martensitic Transformationmentioning
confidence: 88%
See 1 more Smart Citation
“…Urbassek and his coworkers [3,4] studied the strain induced solid-solid phase transition in bcc-Fe thin films and reported a rich variety of phenomena such as back transition to the bcc phase and grain reorientation at high strains. Recently, Meiser and Urbassek [19] investigated thermally induced phase transition in Fe thin slabs with different orientated surfaces using the Meyer-Entel potential [20], which is widely used in studies of the phase transition, both in bulk-dominant and surface-dominant systems. The authors discussed the results from the aspects of the surface energy and transition pathway.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, the phase transition in Fe thin films with three inactive free surfaces under shear deformation will be studied based on the results of [19]. We aim to check whether the applied shear deformation will induce the austenitic/martensitic phase transition.…”
Section: Introductionmentioning
confidence: 99%